Chapaleofú Stream Basin: agriculturization and effect of the chlorpyrifos insecticide on a non-white species - Pena-Gómez, Paula Rocío; Fernández-San Juan, Rocío; Somoza, Ailin; Vazquez, Patricia; Cortelezzi, Agustina (Ecosistemas y Recursos Agropecuarios, 2022)
Agriculturization constitutes a cause of transformation in the territories. The current prevailing model of agriculture, based on the application of pesticides to keep the crop healthy and without competition, not only affects the target species but also non-target species, impacting local biodiversity and the proper functioning of ecosystems. The objective of this work was to analyze changes in land use in the Upper Basin of the Chapaleofú Stream, and determine the toxicity of chlorpyrifos on a non-target species. For this, supervised classified images (years 1989 and 2019) of Tandil district (Buenos Aires, Argentina) were comparison and Lethal Concentration 50 (LC50) of the insecticide chlorpyrifos on the mollusk Physa acuta at 96 hours of exposure was determined. A 74.35% advance of the land destined for agricultural activities was detected, which shows the process of agriculturization. Physa acuta has an LC50 of 0.55 mg L−1, presenting at the same time sublethal effects, despite being a species tolerant to the chemical in question. Regarding the conclusions, more studies are required to generate information on the impact of the multiple chemicals used in agricultural activity, considering longer exposures and with more sensitivity species.